Seasonal moisture sources and the isotopic composition of precipitation, rivers, and carbonates across the Andes at 32º-35.5°S - Hoke, Gregory D. (2013)
Constraining the influence of different moisture sources across the flanks of mountain ranges is important for understanding tectonic, geomorphic, and paleoclimate problems at geologic timescales, as well as evaluating climate change and water resources on human time scales. The stable isotope compositions of stream waters and precipitation are an ideal tool for this task. This study reports the results of a 2 year monthly precipitation sampling campaign on the eastern flank of the Andes in the Mendoza Province of Argentina, which began in September 2008. A total of 104 precipitation samples spanning some 2500 m of relief from nine sites were analyzed for δD and δ18O. In addition, 81 samples from Andean rivers collected on both sides of the range in 2002 and 2007 were analyzed. We employ a Rayleigh isotope fractionation modeling approach to explore spatial and temporal variations in precipitation and river water compositions. The results indicate that precipitation on the eastern slopes of the Andes at ~33°S, at elevations above 2 km, is largely derived from a westerly, Pacific-source component and a mixture of easterly and westerly sources below 2 km. Further south at ~35°S, river water compositions exhibit a strong winter influence. At 33°S, rivers have an isotopic minimum of ~ −18? across the core of the range, which has an average elevation of 4000 m, and are topographically offset from similar isotopic values of precipitation by +1000 m. Comparison of precipitation and river water data with temperature-corrected δ18O estimates from pedogenic carbonates illustrates that carbonates capture the range of variability observed in modern precipitation and Rayleigh fractionation models.